2021
DOI: 10.3892/ijmm.2021.4968
|View full text |Cite
|
Sign up to set email alerts
|

Propofol maintains Th17/Treg cell balance and reduces inflammation in rats with traumatic brain injury via the miR‑145‑3p/NFATc2/NF‑κB axis

Abstract: Propofol is a commonly used intravenous anesthetic. The aim of the study was to examine the mechanism of propofol in traumatic brain injury (TBI) by regulating interleukin (IL)-17 activity and maintaining the Th17/Treg balance. A rat model with moderate TBI was established using the weight-drop method. Rats with TBI were regularly injected with propofol and their brain injuries were monitored. The peripheral blood of rats was collected to measure the Th17/Treg ratio. MicroRNA (miR)-145-3p expression was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…At present, the treatment of craniocerebral trauma is mainly surgery, but surgery is traumatic treatment, so the brain function and brain tissue will have a certain impact, so the choice of narcotic drugs is particularly important [ 6 ]. Studies have shown that propofol, as an anesthetic for preoperative induction and maintenance, can maintain the balance of cerebral oxygen supply and demand, thus playing a role in brain protection and can reduce the level of oxygen free radicals in patients with head trauma, thus reducing brain injury, with good clinical efficacy [ 7 , 8 ]. However, in the present clinical use of propofol in patients with craniocerebral trauma with most of the patient's general information and doctor's clinical experience, the lack of the previous medical data makes the doctor cannot combine the patient information for fine adjustment of the dose of propofol, resulting in some patients to regain consciousness with extension or no ideal improvement in indicators and cannot achieve the expected goal [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the treatment of craniocerebral trauma is mainly surgery, but surgery is traumatic treatment, so the brain function and brain tissue will have a certain impact, so the choice of narcotic drugs is particularly important [ 6 ]. Studies have shown that propofol, as an anesthetic for preoperative induction and maintenance, can maintain the balance of cerebral oxygen supply and demand, thus playing a role in brain protection and can reduce the level of oxygen free radicals in patients with head trauma, thus reducing brain injury, with good clinical efficacy [ 7 , 8 ]. However, in the present clinical use of propofol in patients with craniocerebral trauma with most of the patient's general information and doctor's clinical experience, the lack of the previous medical data makes the doctor cannot combine the patient information for fine adjustment of the dose of propofol, resulting in some patients to regain consciousness with extension or no ideal improvement in indicators and cannot achieve the expected goal [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we demonstrated the positive effects of propofol on antioxidant/oxidant balance with MDA, GSH, TNF-α, IL-6 levels. In various previous studies conducted, it has been shown that propofol prevents apoptosis, has anti-infl ammatory and antioxidant effects and has taken its place in the literature (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Based on this feature on propofol, we investigated whether it has a curative effect on neurotoxicity by developing a peripheral neurotoxicity model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its anesthetic effects, it has been reported in previous studies that it protects cells and tissues from oxidative stress, reduces apoptosis and infl ammation, and protects against hypoxic/ischemic-induced neuronal damage (9)(10)(11)(12)(13). In a study conducted on rats with traumatic brain injury in the literature, the neuroprotective and anti-infl ammatory effects of propofol were emphasized (14). Propofol has lipid peroxidation inhibitory effects as well as reactive oxygen species scavenging effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a model of severe, penetrating TBI, intravenous delivery of simvastatin provided significant protection against injury-induced cognitive dysfunction and reduced TBI-specific serum levels of IL-17A 53 . More recently, propofol, a commonly used anesthetic, alleviated brain injury in rats with TBI and maintained the Th17/Treg balance 54 . Notably, IL-17A derived predominantly from microglia has also been implicated in the pathobiology of various neurodegenerative diseases such as Alzheimer’s and Parkinson’s’ disease 55 .…”
Section: Discussionmentioning
confidence: 99%